EVALUASI DAN PERUMUSAN REKOMENDASI SENAYAN LIBRARY MANAGEMENT SYSTEMS PERPUSTAKAAN MENGGUNAKAN FRAMEWORK COBIT4.1 - Lilis Aminawati; Sri Siswanti; Setiyowati Setiyowati (STMIK Sinar Nusantara, 2019)
Senayan Library Management Systems (SLiMS) is a licensed open source library management system software under the GPL v3. Evaluation of the system process needs to be done especially on the data storage and data processing since both are important in managing data in the library of STIE AUB of Surakarta. The purpose of this study is to determine the maturity level of Senayan Library Management Systems (SLiMS) and provide system recommendation using the domain of Delivery and Support 1 (DS1) and Delivery Support 11 (DS11) with COBIT Framework 4.1. The methods used were observation, interview, literature study and questionnaire. The questionnaires were given directly to the respondents related to the system users, and the performance of the system was carried out by using maturity levels to produce recommendations at the library of STIE AUB Surakarta.